Utilization of Rotten Tomato Juice and Starfruit Juice with the Addition of Potassium Hydroxide in Biobattery Production - Sardewi, Tri; Amanah, Tria Rizki; Rusdianasari, Rusdianasari; Junaidi, Robert; Hasan, Abu (AJARCDE (Asian Journal of Applied Research for Community Development and Empowerment), 2025)
Indonesia's dependence on fossil fuels underscores the need for the development of environmentally friendly alternative energy sources. This research examines the utilization of rotten tomato waste (Solanum lycopersicum) and starfruit (Averrhoa bilimbi L.) juice as natural electrolytes in the production of bio-batteries, with the addition of potassium hydroxide (KOH) to enhance their performance. Both materials contain organic acids such as citric acid and ascorbic acid, which support electrochemical reactions. The experimental variations included electrolyte solution volumes of 200–400 mL and KOH concentrations of 0.1 M, 1.0 M, and 2.0 M. The parameters tested included pH, conductivity, voltage, current, power, capacity, and the duration of the LED light, as specified in SNI IEC 60086-1:2015. The results show that for rotten tomato extract, the optimal combination of 350 mL with 2.0 M KOH yields the highest conductivity of 15.37 mS/cm and a capacity of 2.87 mAh. For starfruit juice, the optimal combination of 200–250 mL with 1.0 M KOH provides the highest capacity. The addition of KOH generally increases conductivity and power output, but high concentrations (2.0 M) in starfruit extract reduce efficiency due to over-ionization. This research proves that rotten tomato waste and starfruit juice with the addition of KOH have the potential to be efficient, inexpensive, and environmentally friendly bio-battery raw materials and support the utilization of organic waste as a renewable energy source. Contribution to Sustainable Development Goals (SDGs):SDG 7: Affordable and Clean EnergySDG 13: Climate Action